2015
DOI: 10.1016/j.jmb.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The Code for Directing Proteins for Translocation across ER Membrane: SRP Cotranslationally Recognizes Specific Features of a Signal Sequence

Abstract: The signal recognition particle (SRP) cotranslationally recognizes signal sequences of secretory proteins and targets ribosome-nascent chain complexes (RNCs) to the SRP receptor in the endoplasmic reticulum membrane, initiating translocation of the nascent chain through the Sec61 translocon. Although signal sequences do not have homology they have similar structural regions: a positively charged N-terminus, a hydrophobic core and a more polar C-terminal region that contains the cleavage site for the signal pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 78 publications
4
71
0
1
Order By: Relevance
“…The kinetics of formation of specific key sub-domain structures should be probed directly, in situ, on the background of the rest of the chain, where mutual influences exist. The possible significance of the loop closure effect in folding in vivo is an intriguing question that might be addressed with currently available FRET and timeresolved fluorescence methods [77,[211][212][213][214]. Co-translational folding of nascent polypeptides on the ribosome is a subject of a major field of current research.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of formation of specific key sub-domain structures should be probed directly, in situ, on the background of the rest of the chain, where mutual influences exist. The possible significance of the loop closure effect in folding in vivo is an intriguing question that might be addressed with currently available FRET and timeresolved fluorescence methods [77,[211][212][213][214]. Co-translational folding of nascent polypeptides on the ribosome is a subject of a major field of current research.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Pex7 the binding groove is narrower compared to the other receptors, which is in agreement with its binding of peptides with a well-defined consensus sequence, whereas Tom20 and Srp54 require more flexibility to enable binding of peptides with variable primary sequence. Moreover, the helical element encoding the PTS2 (I) appears longer when compared to that encoding the presequence (J) or the signal peptide (K), although on average the α-helical elements should have comparable length (Gierasch, 1989;Moberg et al, 2004;Kunze et al, 2011;Nilsson et al, 2015). However, this might be due to the tight cargo binding of Pex7 in the presence of the co-receptor (not shown), which forces the peptide into a well-defined structure.…”
Section: Comparative Summarymentioning
confidence: 99%
“…Detailed analysis of available signal sequence revealed that signal peptides are usually rich in hydrophobic residues with a core element composed of a positively charged domain, a hydrophobic domain of 8-12 amino acids and a polar Cterminal region, which have been denominated as [n]-domain, [h]-domain, and [c]-domain (Briggs and Gierasch, 1984;von Heijne, 1985;Gierasch, 1989) (Figure 2D). Individual changes in the charge pattern of the [n]-domain or of the [c]-domain had little effect, whereas a shortening of the [h]-domain had severe consequences for the import of a reporter protein (Nilsson et al, 2015) and the presence of several positive charges in the [c]-domain was also detrimental (Fujita et al, 2011). According to their hydrophobic character signal peptides are often not soluble in water, but form α-helical domains in hydrophobic environment (Briggs and Gierasch, 1984;Yamamoto et al, 1990), which can be depicted on a helical wheel projection for a typical signal peptide ( Figure 2H).…”
Section: Targeting Signals For the Ermentioning
confidence: 99%
“…The Sec secretion pathway can also utilize a co-translational mechanism of export that couples translation of proteins by the ribosome with secretion through the SecYEG channel [the signal peptide recognition particle (SRP) pathway]. The SRP pathway relies on the SRP particle, which recognizes an N-terminal signal peptide with highly hydrophobic core during protein secretion and the binding affinity of the SRP particle for signal peptides increases with the hydrophobicity of the h-region of signal peptides (Green and Mecsas 2016; Nilsson et al 2015). …”
Section: Introductionmentioning
confidence: 99%